2013 IEEE International Conference on Computer Vision Workshops 2013
DOI: 10.1109/iccvw.2013.93
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Reduction of Large Image Databases for Location Recognition

Abstract: For some computer vision tasks, such as location recognition on mobile devices or Structure from Motion (SfM) computation from Internet photo collections, one wants to reduce a large set of images to a compact, representative subset, sometimes called "keyframes" or "skeletal set". We examine the problem of selecting a minimum set of such keyframes from the point of view of discrete optimization, as the search for a minimum connected dominating set (CDS) of the graph of pairwise connections between the database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The proposed method is validated using two datasets sourced from Flickr [23]. The first one, MERGED, was kindly provided by the authors of [5]. It consists of 9,469 images from three different landmarks: roughly one third of them depicts the Fontana di Trevi in Rome, another third the Duomo in Milan, and the last third the Old Town Square in Prague.…”
Section: Methodsmentioning
confidence: 99%
“…The proposed method is validated using two datasets sourced from Flickr [23]. The first one, MERGED, was kindly provided by the authors of [5]. It consists of 9,469 images from three different landmarks: roughly one third of them depicts the Fontana di Trevi in Rome, another third the Duomo in Milan, and the last third the Old Town Square in Prague.…”
Section: Methodsmentioning
confidence: 99%
“…While heuristics for the selection as used by Li et al (2010) and Dymczyk et al (2015b) provide good results, it has been shown by Mauro et al (2014) and Havlena et al (2013) that optimization-based approaches can provide gains especially under high compression rates. These approaches target picking the most informative landmarks while ensuring that every camera must observe at least N thres landmarks to provide coverage across the model area.…”
Section: The Need For Model Compressionmentioning
confidence: 99%
“…One popular visual map compression method is based on optimization approach, formulating the selection problem as a programming problem. For computer vision tasks, location recognition is similar with the localization, and ILP was used in data database to select the most compact subset of images to achieve recognition [13]. Park et al [8] proposed the quadratic programming (QP) method to solve the visual map compression, which is a baseline for further 3D point cloud reduction.…”
Section: Related Workmentioning
confidence: 99%